2020
DOI: 10.1186/s12967-020-02563-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated macrophage-like cells and prognosis of esophageal cancer after chemoradiation therapy

Abstract: Background Cancer Associated Macrophage-Like cells (CAMLs) are polynucleated circulating stromal cells found in the bloodstream of numerous solid-tumor malignancies. Variations within CAML size have been associated with poorer progression free survival (PFS) and overall survival (OS) in a variety of cancers; however, no study has evaluated their clinical significance in esophageal cancer (EC). Methods To examine this significance, we ran a 2 year prospective pilot study consisting of newly diagnosed stage I-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Most intriguing is the nature of these giant cells, which have been identified in patients with cancers but not in healthy donors [ 33 ]. They were given different names: circulating hybrid E/M cells, giant epithelioid cells, fusion-derived epithelial cancer cells, tumor-macrophage fusion cells (TMFs), macrophage-tumor cell fusion cells (MTFs), or cancer-associated macrophage-like (CAMLs) cells [ 22 , 30 , 32 , 33 , 34 , 35 , 36 ]. This shows that the origin of g - aCTCs is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most intriguing is the nature of these giant cells, which have been identified in patients with cancers but not in healthy donors [ 33 ]. They were given different names: circulating hybrid E/M cells, giant epithelioid cells, fusion-derived epithelial cancer cells, tumor-macrophage fusion cells (TMFs), macrophage-tumor cell fusion cells (MTFs), or cancer-associated macrophage-like (CAMLs) cells [ 22 , 30 , 32 , 33 , 34 , 35 , 36 ]. This shows that the origin of g - aCTCs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified these large cells as cells related to the macrophage lineage, describing them in a broad way as giant macrophages (CAMLs, MTF, or MFT) that contain phagocytosed epithelial debris [ 22 , 31 , 33 , 34 , 35 , 38 ]. These cells indeed express CD14 or CD11c, two markers of the macrophage/myeloid lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a second type of tumor associated cell has been discovered, the cancer associated macrophage-like cell (CAML). This cell has been described as a pro-tumorigenic giant myeloid cell found in circulation, along with CTCs in several solid tumor cancers, including PC [6][7][8][9][10]. CAMLs have been shown to reliably predict progression and survival in PC, which may also be related to CTC intravasation into circulation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This cell has been described as a pro-tumorigenic giant myeloid cell found in circulation, along with CTCs in several solid tumor cancers, including PC [6][7][8][9][10]. CAMLs have been shown to reliably predict progression and survival in PC, which may also be related to CTC intravasation into circulation [8][9][10][11]. Another circulating tumor associated cell (TAC), that has been implicated in the progression of PC, is the epithelial-mesenchymal transition cell (EMT) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the main treatment method for ESCC is a combined treatment of radiotherapy, chemotherapy, and surgery [ 3 ]. The emergence of drug resistance in molecular targeted therapy leads to poor clinical efficacy in patients with ESCC [ 4 , 5 , 6 , 7 ]. According to statistics, from 2010 to 2016, the 5‐year survival rate remains poor (20%) [ 1 ], and the mortality rate has remained high [ 8 , 9 , 10 ].…”
mentioning
confidence: 99%